The role of tumour morphology in assigning HPV status in oropharyngeal squamous cell carcinoma. (June 2020) - Molony, Peter; Werner, Reiltin; Martin, Cara; Callanan, Deirdre; Nauta, Irene; Heideman, Daniëlle; Sheahan, Patrick; Heffron, Cynthia; Feeley, Linda
Highlights: Precise human papilloma virus status is vital for oropharyngeal cancer management. Morphology with p16 IHC and HPV DNA testing if discordant correlates with survival. This combined approach is superior to morphology or p16 immunohistochemistry alone. It may be a cost-effective additional test to address false positive p16 results. Abstract: Objectives: There is no consensus on the optimal approach to human papilloma virus (HPV) testing in oropharyngeal squamous cell carcinoma (OPSCC). Our objective was to classify OPSCC as HPV positive or negative based on (1) morphology alone, (2) p16 status alone, (3) combined morphology and p16 status with additional HPV testing in discordant cases in keeping with 2012 College of American Pathologists (CAP) guidelines (combined approach), and to evaluate and compare survival outcomes. Materials and Methods: Retrospective review of 168 patients, 146 with OPSCC and 22 with cervical SCC of unknown primary site (SCCUP). Morphology was classified as keratinizing or non-keratinizing, p16 immunohistochemistry (IHC) performed and additional HPV DNA PCR testing undertaken in cases in which morphology and p16 status were discordant. Survival statistics were evaluated and compared for the 3 different approaches to classification. Results: On univariate analysis all 3 classification methods significantly predicted for overall survival (OS). Both p16 status and the combined approach also predicted for disease specific survival (DSS), whereas morphology fell just outside significance (p = 0.06). On multivariate analysis only the combined approach retained significance for both OS and DSS, whilst morphology was also significant for DSS. Conclusions: Our findings confirm that tumour morphology significantly predicts for survival in OPSCC. However, we found combined tumour morphology and p16 IHC, with additional testing for discordant cases to be superior to either morphology or p16 IHC alone. Further study is required to establish the optimal testing method for HPV in OPSCC particularly in low prevalence populations.